METABOLIC SYNDROME IN URBAN AND RURAL POPULATION OF GREATER NOIDA NATIONAL CAPITAL REGION OF INDIA - Sharma, Manoj Kumar; Pandey, Sonali; Nagtilak, Suryakant (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to evaluate the prevalence of metabolic syndrome (MetS) and to define its predictors in urban and rural patients presenting to tertiary care hospitals located in Greater Noida district Gautam Budh Nagar, India. Methods: A total of 367 participants recruited in the study, aged 20–55 years, comprising, 290 patients (149 rural and 141 urban) and 77 healthy age, sex-matched controls from the study area. Anthropometric, clinical and laboratory examination information was obtained. MetS was defined as per the National Cholesterol Education Program, Adult Treatment Panel III (NCEP, ATP III) report. Results: There were significant differences in biochemical and anthropometric measurements between control and patient population (p<0.05). There was a substantial difference in the prevalence of MetS among male and female patient population of urban as well as rural areas. As per NCEP, ATP III criteria, the prevalence of MetS in urban patient population was 21.7% in male and 27.8% in female whereas rural male and female exhibited 13.8% and 18.8% of MetS, respectively. Waist circumference was found as the strongest predictor of MetS among the patient population. Conclusion: Rapid urbanization of the cities is affecting the village life and indicating toward a major burden of diseases associated with MetS. A higher prevalence of MetS in female irrespective of the area of residence needs major health-care policy change. There is an urgent need to address this issue by adopting healthy eating, physical exercise, and weight reduction.